Study on the mechanical behavior of construction and demolition waste-based geopolymers under high-temperature conditions - Yiming Chen (Journal of Asian Architecture and Building Engineering, 2024)
This study explores the mechanical properties of geopolymers derived from construction and demolition waste exposed to high temperatures. Geopolymers were exclusively crafted from waste bricks or ceramic tiles, activated with potassium hydroxide/sodium silicate solution. We assessed compressive deformation during 850°C − 1050°C exposure and residual strength post 600°C − 1050°C exposure (simulating ISO 834 curve). Microstructure and bulk properties were also examined.Both geopolymers exhibitecd consistent post-fire behavior. Compressive strength decreased between 600°C and 800°C but rebounded at 1050°C, surpassing initial levels. At 1050°C, density dropped by 8–9%, with a 7–10% mass loss. In fire tests, ceramic tile-based geopolymers displayed plastic deformation at all tested temperatures without macro-fractures, whereas brick-based geopolymers remained elastic up to 1000°C with evident macro-fractures.These findings suggest the potential of both geopolymers as fire-resistant building materials, contributing to advancements in construction materials.